Female Board Representation and Corporate Performance: A Review and New Estimates for Australia - Nicholas Bayly; Robert Breunig; Chris Wokker (Institute of Labor Economics (IZA), 2023)
Despite a conventional wisdom that female board members positively impact firm performance, a thorough examination of the research to date reveals no consensus that female board members have either a positive or negative effect on firm performance. We build the largest dataset of Australian board appointments assembled to date. We use our data to demonstrate how difficult it is to replicate existing research, with one example from Australia and one from the US. Using event studies and regression analyses we demonstrate that there is little evidence that female board representation affects firm financial performance.
Keywords: J16; N20; G32; 330; firm performance; board of directors; gender representation; female directors